Análise dos serviços de atenção secundária na especialidade de endodontia de municípios de Minas Gerais: percepções de usuários e endodontistas - Jose Leonardo Barbosa Melgaco da Costa (2012)
The evaluation of the health services is an important tool of management in the evolution and construction of the service, to guide and plan the decisions. In endodontics, the introduction of rotary nickel-titanium instruments facilitated the shaping of root canalssystem, with shorter time and greater clinic efficiency, showing better quality in the filling of the root canals. These facts results in a lower fatigue for both patients and for professionals, allowing to assist a great number of patients with a high technical quality. This study evaluated the secondary care services in endodontics, in the Dental Specialty Centers at three cities of Minas Gerais, Brazil, according patients and professional perceptions, considering the instrumentation technique employed: hand or rotary. Semistructured interviews with 10 patients and 6 professionals, direct observation and field diary were used. The interviews were recorded by audio-tape, full transcribed and analyzedqualitatively. The patients perception was restricted to access and quality of endodontic treatment, mainly the treatment received, without differentiate the technique employed. The professionals perception focused the service and the technology employed. The number ofsessions to conclude the endodontic treatments, with the new technology, implied fewer sessions only to molars group, while in the others groups of teeth there were no differences in the sessions number regardless the instrument employed. The insertion of rotaryinstrumentation in the public service was approved, since accompanied by training professional. The results appointed that the patients evaluation about the endodontics service should not be considered separately, but as an essential part to plan strategies for serviceimprovement. The professional evaluation showed as an important fool to management and plan strategies of improvement in service, emphasizing the importance of the insertion of new technology in the public service of endodontic associated to the professional training, toimprove this insertion.